Cadre Training for Early Detection of Hypertension with Booklets in Kampung Parung Ponteng Rw 07, Desa Tajur, Citeureup, Bogor - Rochmayanti; Sapta Prayoga; Zakia Saleh Dawil (Jurnal Pengabdian Masyarakat Bestari, 2022)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg (Smeltzer & Bare, 2017). The purpose of holding Community Service is to increase the ability of cadres to prevent hypertension and public awareness of chronic hypertension. The participants of this training were RW 07 cadres with a total of 5 people. This activity was carried out by providing health education about hypertension and its management with a booklet for 1 week, before the implementation was given the pretest contents of the booklet and after 10 days posttest. The results of this Community Service found that there was an increase in cadres' knowledge of hypertension and its management with booklets of around 67%. Cadres respond well to explanations about 100% hypertension, cadres participate in activities from start to finish, so that cadre knowledge increases and they can explain knowledge of early detection of hypertension when carrying out blood pressure checks in the community of Rt 01 and RT 02.